Privacy-Preserving and Gas-Efficient Car Service Record Management Using Adaptive User-Resilient CKKS Homomorphic Encryption and Blockchain - Yasmin, S.; Devi, G. Shree (Engineering, Technology & Applied Science Research, 2026)
Many car-selling and car-service websites have sprung up as a result of the automobile industry's quick digitization, offering consumers convenient access to vehicle details and transaction histories. Due to privacy and data management restrictions, these platforms typically show only the most basic information about an automobile, including its make, model, year of manufacture, mileage, price, and restricted ownership history, with Important service records, warranty claims, and part replacements typically left out. In addition to decreasing buyer transparency, the lack of thorough records makes it more difficult for automobile owners, dealers, and repair facilities to securely share data. Furthermore, data stored on centralized web servers is susceptible to loss of integrity, illegal changes, and data breaches. To overcome these obstacles, this study presents a unique method for the safe maintenance of comprehensive auto service records that combines blockchain technology with the AURA-CKKS homomorphic encryption scheme and the Brotli compression algorithm for storage optimization. The blockchain holds metadata, transaction logs, and Content Identifiers (CIDs) for traceability, while the InterPlanetary File System (IPFS) houses the compressed and encrypted data for decentralized and impenetrable storage. A Token-based Key Management System (TKMS) is utilized to securely distribute and maintain encryption keys among authorized stakeholders. The proposed architecture uses blockchain technology to ensure data immutability, AURA-CKKS encryption to maintain secrecy, and Brotli compression to reduce storage overhead, allowing all stakeholders to access verifiable and impenetrable vehicle histories while protecting data privacy. According to experimental results, the suggested framework decreases blockchain gas consumption by roughly 95% when compared to baseline raw on-chain storage, and by 94% compared to AURA-CKKS-based on-chain encryption. Brotli compression offers 43% reduction in data size. Additionally, in high-load circumstances, transaction confirmation time is decreased by 60%, query latency is reduced by 75%, and execution time is reduced by almost 55%. Due to adaptive bootstrapping and decentralized key verification, security testing reveals strong resilience (scores 4-5) against replay, Sybil, and key-theft attacks. These results confirm that the proposed architecture, combining AURA-CKKS, IPFS, TKMS, and blockchain, greatly improves computational efficiency, scalability, and privacy, providing a verifiable and tamper-proof vehicle-record management solution appropriate for next-generation automotive data ecosystems.